The Relationship Between Listening Strategy Performance and Critical Listening Ability of Indonesian Students - Arono Arono (Institut Agama Islam Negeri Imam Bonjol Padang, 2015)
It is believed that students’ critical listening ability can be improved through proper listening strategy performance. This action research (Fraenkel Wallen, 2007) was conducted in line with the assumption that students of Indonesia Literature and Language Education, Bengkulu University and Bengkulu Muhammadiyah University could reach proficient level provided that they were taught properly. The goal of this research was to reveal listening strategy performance related to students’ critical listening ability. The result of the research showed that the relationship between listening strategy performance and critical listening ability of students tended to be directly proportional in which high students’ listening strategy performance tended to be followed by high critical listening ability and vise versa. Students’ listening strategy performance in improving students’ critical listening ability was able to (1) effective activities, students create active, effective, and creative learning process independently in measuring and developing in each step of listening learning model, (2) enough listening learning media can improve students’ critical listening skill (3) critical listening strategy performance can increase students’ critical listening ability. Copyright © 2015 by Al-Ta'lim All right reserved